Islam and universal declaration of human rights: accord or discord? - Ishak, Mohd. Shuhaimi (IDOSI Publications, 2014)
The issue of human rights is a matter of growing concern for Muslims and Non-Muslims. The schemes of human rights sponsored by the United Nations, in the aftermath of the World War II, espouse the idea of rights backed by constitutional laws and international law binding on all nations. Contrary to what might otherwise be thought or perceived human rights in Islam possess certain distinctive features similar to the Universal Declaration of Human Rights (UDHR) 1948. The prevailing image of discord between Islam and UDHR is a distorted one as the differences between them can be recognized and acknowledged while the common grounds are properly accorded. Instead of accentuating the differences and antagonisms, the common relationship between Islam and UDHR needs to be consistently debated and highlighted as both have the common objectives to guarantee human rights. This is so as the direct impact of the relationship concerns with the integral and constitutive component of development processes in human life. This paper attempts to shed light on the commonality between the two systems as anchored on moral domains of Islamic principles which have many common grounds are articulated.